Indeks Subjek Volume 32, Tahun 2012 - Indeks Subjek Volume 32, Tahun 2012 (agriTECH, 2012)
Acceptance 98ACE inhibitor 259Acetobacter xylinum 98Aloe vera drink 73Altitudes 200Amelogenin 371Antibacterial 309Antioxidant 73, 167Antioxidant activity 249, 295, 392Aroma 98, 105Artifi cial neural network 411ASLT 301Autonomous agricultural vehicle 144